Improving Listening Skill to Fairytales Using A Hand Puppets Media - Desy Sugianto; Dwi Cahyadi Wibowo; Ursula Dwi Oktaviani (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2017)
The purpose of this research was to describe the increase the ability of listening to fairy tales using hand puppets media in grade III State Elementary School 16 Sungai Ringin Sintang year 2016/2017. The approach of this study was a qualitative descriptive form of classroom action research. The result showed that (1) the puppets media enhanced students’ listening skills very well, seen from students’ active and enthusiastic participation; (2) the listening skill in the first cycle gained the average of 63.78 and reached 72.42 in cycle two. This showed an increase of learning outcome from the first to the second cycle of 8.64 points. The general completeness level in the first cycle was 60.71% with satisfactory categories and in the second cycle reached 85.71% in both categories; (3) The response of students to the application of a hand puppet media was very good. This shows that the use of hand puppets media while listening to fairy tales is a way that can attract students’ attention.